PENGARUH KONFLIK DAN STRES KERJA TERHADAP KINERJA MELALUI KOMITMEN PADA STAF SEKRETARIAT KOMISI PEMILIHAN UMUM PROVINSI JAWA TIMUR - Anam, Choirul; Prasetyo, Indra (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
The purpose of this research is to determine the effect of conflict and work stress through organizational commitment on the performance of the East Java Province General Election Commission Secretariat Staff. This research uses an associative quantitative research design using a questionnaire of 70 respondents, then the results of the questionnaire are analyzed using the smart PLS 4 program. The results of this research are 1) Work conflict has a significant effect on organizational commitment. 2) Stress has a significant effect on organizational commitment. 3) Organizational commitment has a significant effect on performance. 4) Work conflict has a significant effect on performance. 5) Stress has a significant effect on performance. 6) Work conflict and work stress have a positive but not significant effect through organizational commitment to performance. 7) Work conflict and work stress have a positive but not significant effect through organizational commitment to performance.